Physical analysis of an operation of GaInAs/GaAs quantum-well vertical-cavity surface-emitting diode lasers emitting in the 1.3-μm wavelength range - Sarzała, Robert P. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Comprehensive three-dimensional self-consistent optical-electrical-thermal-gain physical modelling is used to simulate room-temperature continuous-wave performance characteristics of GaInAs/GaAs lasers emitting in the 1.3-μm wavelength range. The simulation takes into consideration all physical phenomena crucial for a laser operation including all important interactions between them. A real possibility to design high-performance 1.26-μm GaInAs/GaAs quantum-well vertical-cavity surface-emitting diode lasers (VCSELs) with the aid of a currently available technology is shown. Their outputs are much higher than in the case of their quantum-dot version. Methods to shift the emitting wavelength range of 1.3 μm are discussed and anticipated performance characteristics of such a 1.3-mm VCSELs are determined.
Optica Applicata, Vol. 35, 2005, nr 2, s. 225-240
Keywords: optyka; semiconductor laser; VCSEL; GaInAs/GaAs QW